INSPIRASI KONSEP KEMANUSIAAN KRISTIANI DALAM SURAT PAULUS KEPADA FILEMON - Tonius Hia (Jurnal Teologi (Journal of Theology), 2023)
This article explores Paul’s ideas about humanity in his letter to Philemon. The issue discussed in the present correspondence pertains to Onesimus, an enslaved individual who absconded from the domicile of Philemon. As an enslaved person, Onesimus prefers to meet Paul in prison more than anywhere else. Philemon was a follower of Christ, who Paul had converted. However, Philemon is a prominent individual who possesses an enslaved person that goes by the name of Onesimus. Paul has identified a problematic issue with Philemon about his slave. Paul teaches love among them by defending Onesimus’ humanity without having a conflict with Philemon. Upon reflecting on the matter, Paul realizes that Philemon exercises a harmful employer over Onesimus. Therefore, Paul sent a letter to Philemon as a herald of Christ.  This letter remarks on the request to Philemon to accept Onesimus as his brother and pardon him as a form of acquittal. Despite Paul’s proposition’s weighty obligation, Philemon, as a Christian, must comply. Additionally, the author employs the historical-critical method to ascertain the interpretation of the concept of humanity as articulated by Paul in his epistle to Philemon. Through this approach, it is possible to offer a comprehensive explanation of the text of the Scriptures in relation to its historical and contextual underpinnings of authorship.